Development of HOTS (High Order Thinking Skill) Based News Text Assessment Instrument for 8th Grade Students in SMP Muhammadiyah 7 Medan - Dzu Mirratin Firda Hidayat; Abdurahman Adisaputera; Isda Pramuniati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this research is to analyze the development of HOTS (High Order Thinking Skill) based news text assessment instruments for for 7th Grade Students in SMP Muhammadiyah 7 Medan. The study was conducted at SMP Muhammadiyah 7 Medan. This research was conducted in the even semester of the 2018/2019 school year. This type of research is research and development or Research and Development (R&D). This research is called R&D, by adopting eight steps of R&D research according to Sugiyono (2014: 137). The results of this study indicate that students' high-level thinking skills obtained an average score of 51.42. This value is in the medium category because the standard value is met 40 <x total score ≤ 60. The measurement results of the assessment instrument based on Higher Order Thinking Skill in the dimensions of students' persuasive text knowledge obtained superior conceptual ability results with a percentage of 76% in the sufficient category, followed by factual abilities with the percentage of 60% is in the sufficient category, students 'procedural knowledge is 58% with low category, and students' knowledge that is metacognitive there are 59% with enough category. Thus, it can be stated that the eighth grade students of SMP Muhammadiyah 7 Medan have advantages in the conceptual dimension of knowledge and the ability to think at a high level with a medium category, ie students must be accustomed to working on questions based on Higher Order Thinking Skills so that students' abilities increase.